Pengaruh Digitalisasi Dalam Efektifitas Pengelolaan Kearsipan Dokumen Kepesertaan BPJS Ketenagakerjaan Cabang Meulaboh - Mau’izah, Mau’izah; Damrus, Damrus (CV RIFAINSTITUT, 2022)
This study aims to determine the effect of digitalization on the effectiveness of archive management of BPJS Ketenagakerjaan membership documents in the Meulaboh Branch. This research method is descriptive qualitative. The results of this study indicate that the BPJS office in managing archives uses three systems, namely the manual system, the digitization system and the latest system. Archival storage is very important for the smooth running of organizational activities that are useful as a source of information and a memory center. Unfortunately, the appreciation of archives is still very low so it is not managed properly. Digitization is closely related to archive preservation. The process of digitizing archives at the BPJS Meulaboh branch office has problems in digitizing archives, such as limited human resources, namely the number of staff who digitize archives is still lacking. scanner tool malfunction that must be repaired immediately, and make improvements to web maintenance that often occurs, which affects its work process.